The Influence of Promotions, Brand Ambassadors and Korean Wave on Somethinc Product Buying Interest - S., Ratnah; Putrawan, Muh. Rizah (Cita konsultindo, 2025)
The purpose of this study is to find out how brand Ambassadors, promotions, and Korean waves affect consumers' interest in buying certain products. Utilizing primary data sources collected directly from respondents by distributing online questionnaires, the methodology used is quantitative research. The wider community is the research population. 43 people answered the questionnaire after it was distributed. Quantitative research is the methodology used. Using the SPSS Statistics 25 tool, validity test, T-test, multiple linear regression analysis, and determination coefficient were used in the analysis of this study. The results of the analysis showed that with a t-count value of 4.012 > 1.682 and a significance level of 0.00 < 0.05, promotion had a positive and large effect on buying interest. Meanwhile, customer buying interest is not much influenced by brand ambassadors or Korean Wave. The combined effect of promotions, brand ambassadors, and Korean waves was positive and quite large, impacting customer buying interest by 0.529 or 52.9%. Other variables that were not included in the study had an impact on the rest by 47.1%.